Analysis of the inner rainbands of tropical cyclones over the South China Sea during the landfall process - Xiang, Chunyi; Xu, Yinglong; Lin, Jian; Liu, Shuang (Frontiers in Earth Science, 2022)
Tropical cyclones (TCs) can undergo offshore rapid intensification (RI) shortly before making landfall over the South China Sea (SCS). In this study, the inner rainbands distribution of both RI and non-RI landfall TCs (LTCs) in the SCS during 2015–2020 is examined based on a multi-source merged precipitation dataset. It is found that those RI LTCs exhibit a relatively higher averaged rain rate in the inner core region than that of non-RI LTCs. Both offshore RI cases and non-RI LTCs appear to have an increasing tendency of averaged rain rate after landfall, with the rain rate peak of the RI cases a few hours earlier than that of non-RI cases. By defining an axisymmetric index, the inner rainband evolution of both offshore RI cases and non-RI ones are further discussed. For both categories, most of the axisymmetric rainfall is concentric around the center and over 70% axisymmetric rainfall dominates the inner core region within three times of radius of maximum wind speed (RMW). It is shown that there is an obvious inwards shrinkage of axisymmetric rainfall for both offshore RI and non-RI cases. Analysis of typical RI and non-RI LTCs (1713 Hato and 1714 Pakhar) also shows an increasing rain rate of the inner rainbands soon after landfall, with larger amplitude for RI example than non-RI case. The inner rainbands of 1713 Hato show that a clockwise propagation with maximum enhancement happened at the down-shear left-hand side a few hours after landfall.